Analysis of Chemical Composition of Four Essential Oils by GC MS and its Antibacterial Activity against Human Pathogenic Bacteria - Sivamani, P (International Journal of Pharmaceutical & Biological Archive, 2013)
Analysis of Chemical Composition of Four Essential Oils by GC MS and its Antibacterial Activity against Human Pathogenic Bacteria